The Greek Name of Cinnabar - Rosół, Rafał (Polskie Towarzystwo Filologiczne, 2018)
The paper deals with the Greek word for ‘cinnabar, vermilion’, namely κιννάβαρι(ς) / τιγγάβαρι. After a short introduction regarding the earliest occurrence of the mineral in the Greek world and its earliest description provided by Theophrastus of Eresus, the author discusses all Greek forms and derivatives of the word. Linguistic data coming from Oriental languages is then examined, i.e. Ancient and Modern Persian, Arabic, Saka Khotanese, Chorasmian, Gāndhārī Prakrit, Armenian and others. The following conclusions are drawn from this study: (1) the name of cinnabar is a Wanderwort which was used across a wide area and for a long period of time; (2) the word was probably borrowed into Greek in the late Archaic period; (3) it did not originate from an Iranian language, but from another Oriental language, perhaps used in Asia Minor near Miletus or on the eastern coast of the Black Sea; (4) the Greek forms with τιγγ- are earlier than those with κινν-.
Keywords: cynober; Theophrastus of Eresus